IMPLEMENTASI DECISION TREE BERBASIS ANALISIS TEKNIKAL UNTUK PEMBELIAN DAN PENJUALAN SAHAM - Nugroho, FX. Satriyo Dwi (KINERJA, 2008)
The aim of this research is to develop decision support system using data mining decision tree method that is built base on technical analysis of financial market (EMA, MACD, OBV, RSI, and parabolic SAR). Those indicators are arranged as a trading rule that wi l l help in buying and selling decision. The data used in this research are historical stock price in Jakarta Stock Exchange The result of this research indicates that generally the system can give number of transactions result in capital gains higher than number of transactions result in capital loss. The system also has capability to make decision with average gains are higher than decision with average losses. Investigation to profitability, geometric mean, cumulative wealth index, and sensitivity test to moving average gives the description whether stock can be traded based on technical analysis or not. This system can make easier in making decision for the users/investors that do not have enough knowledge and experiences in financial market.Keywords: decision support system, data mining, decision tree, trading rules, technical analysis.